Development and metamorphic loss of the musculature in larvae of the nudibranch Phestilla sibogae: A functional ontogeny. (27th March 2022) - Croll, Roger P.; Hadfield, Michael G.
Abstract: Developmental programmes for many marine invertebrates include the assembly of muscular systems appropriate to the functions of swimming and feeding in pelagic larvae. Upon metamorphosis, that musculature is often radically re‐organized to meet very different demands of post‐larval life. To investigate the development and fate of musculature in the nudibranch Phestilla sibogae, embryos, larvae and metamorphosing stages were fixed, labelled with phalloidin and examined with confocal microscopy. The resultant images revealed the sequential development of both large retractor muscles and numerous finer muscles that allow the larva to manipulate the velum, foot and operculum. Observations of living specimens at the same stages as those fixed for microscopy revealed the actions of the muscles as they developed. During metamorphosis, muscles with shell attachments disintegrate as the larva transforms into a shell‐less juvenile. Notably, the massive velar, pedal and opercular retractor muscles disappear during metamorphosis in a sequence that corresponds to their loss of function. Other muscles, however, that appear to be important to the embryo and free‐swimming larva persist into juvenile life. The comprehensive and detailed observations of the musculature presented here provide a solid foundation for comparisons with other species with different phylogenies and life histories.